The effect of antibiotics on the in vitro growth response of chrysanthemum and tobacco stem transverse thin cell layers (tTCLs) - Teixeira da Silva, Jaime A; Nhut, Duong T; Tanaka, Michio; Fukai, Seiichi (Scientia Horticulturae, 2003)
Plant tissue culture systems are always under threat of microbial contamination from the air, the tissue culturer, and from the tissue cultured plant itself, and antibiotics can be utilized to eliminate unwanted contaminants from tissue culture. In addition, the genetic transformation of plants requires selection and regeneration of transformed tissues through the use of an antibiotic-degrading gene. This study utilizes a wide range of antibiotic agents to examine their effect on chrysanthemum and tobacco thin cell layer (TCL) tissue culture systems, with an increasing gradient of phytotoxicity being observed: bialaphos ®>chloramphenicol>rifampicin>streptomycin>minomycin>ampicillin>penicillin G=penicillin V, demonstrating that the limiting factor to the use of these agents is in fact the plant. Following the establishment of threshold survival levels, a decrease in explant survival and reduced biomass, malformation of roots and inhibition of shoot formation in chrysanthemum was observed, and further, in the case of tobacco endoreduplication.